(untitled) (Acta Scientiarum. Health Sciences, 2014)
http://dx.doi.org/10.4025/actascihealthsci.v36i1.13184 The objective of this study is to describe a pharmacotherapy form model to monitor patients’ pharmacotherapeutic follow-up (PF) on antiretroviral therapy in a specialized center of Ceará, Brazil. Description comprises its structure up to application. The preparation and application of the PF registration model were carried out by means of a focal group. The following steps were used for the draft: 1. Review of the literature; 2. Diagnosis of place where pharmaceutical care was undertaken; 3. Choice of the PF method; 4. Selection of clinical indicators; 5. Evaluation by a committee of experts; 6. Development of a standard functional procedure with timetable and evaluation frequency of the tool’s different sections or blocks. 7. Pilot study for evaluation of the form with 25 patients. PF form featured six sections comprising patient’s personal data, pharmaceutical anamnesis and records of adherence evaluation, etc. The description and format of the sections are presented in current essay. Further, 322 issues related to antiretroviral drugs were reported during form filling. The multi-section PF form seemed appropriate and applicable for the report of issues related to antiretroviral drugs in HIV positive patients. It was also a helpful guide for pharmaceutical interventions by a multiprofessional team in specialized healthcare settings.